2013
DOI: 10.1038/mt.2012.213
|View full text |Cite
|
Sign up to set email alerts
|

Aging-related Decrease of Human ASC Angiogenic Potential Is Reversed by Hypoxia Preconditioning Through ROS Production

Abstract: Adipose stroma/stem cells (ASC) represent an ideal source of autologous cells for cell-based therapy. Their transplantation enhances neovascularization after experimental ischemic injury. Aging is associated with a progressive decrease in the regenerative potential of mesenchymal stem cells (MSCs) from bone marrow. This work aims to determine the aging effect on human ASC capacities. First, we show that aging impairs angiogenic capacities of human ASC (hASC) in a mouse ischemic hindlimb model. Although no chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 46 publications
2
74
0
1
Order By: Relevance
“…Unlike the controversial embryonic stem cells, MSCs could be isolated from many ethically palatable tissues such as bone marrow [16,17], adipose tissue [17,18], liver [19,20], muscle [21,22], amniotic fluid [23,24], placenta [25,26], umbilical cord blood [16,27], dental pulp [28,29]. However, it is generally observed that the biological activity and therapeutic potency of MSCs correlate inversely with developmental stage of the donor [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Therefore, MSCs from ethically and socially controversial but "young" tissues such as fetal tissues [49] and human embryonic stem cells (ESCs) [50] continue to be investigated for their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the controversial embryonic stem cells, MSCs could be isolated from many ethically palatable tissues such as bone marrow [16,17], adipose tissue [17,18], liver [19,20], muscle [21,22], amniotic fluid [23,24], placenta [25,26], umbilical cord blood [16,27], dental pulp [28,29]. However, it is generally observed that the biological activity and therapeutic potency of MSCs correlate inversely with developmental stage of the donor [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Therefore, MSCs from ethically and socially controversial but "young" tissues such as fetal tissues [49] and human embryonic stem cells (ESCs) [50] continue to be investigated for their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…In physiological concentrations, testosterone and AS can slightly increase the concentration of ROS, which might induce neuronal preconditioning, protecting these cells against further increases in ROS concentration [96,97]. However, in supraphysiological concentrations, AS can significantly increase the ROS bioavailability by mitochondrial and nonmitochondrial mechanisms, resulting in oxidative damage and neuronal apoptosis.…”
Section: Redox Imbalancementioning
confidence: 99%
“…опуб ликовали результаты своих экспериментов с МСК, выделенными из жировой ткани моло дых и старых доноров. Оказалось, что старение снижало способность МСК дифференци-роваться в эндотелиальные клетки, уменьшалась про-дукция VEGF [82]. Гипоксическое прекондиционирова-ние (0,5% О 2 в течение 24 ч) увеличивало синтез VEGF и усиливало способность МСК дифференцироваться в эндотелиоциты.…”
Section: актуальные вопросы патофизиологииunclassified